Implementasi Asas Persamaan Perlakuan Bagi Pasien Rawat Inap DiRumah Sakit Umum Daerah dr. R. Goeteng Taroenadibrata BerdasarkanPeraturan Daerah Nomor 3 Tahun 2020 Tentang Pelayanan Publik DiKabupaten Purbalingga - Puja Kirana; Iskatrinah; Esti Ningrum (Wijayakusuma Law Review, 2023)
This study aims to find out how the implementation of the principle of equality of treatment in public services in thehealth sector at the Regional General Hospital (RSUD) dr. R. Goeteng Taroenadibrata, Purbalingga Regency, and tofind out what factors hinder the hospital in applying the principle of equality of treatment in the health sector toinpatients who use BPJS services (Social Security Administering Body) and patients who use public services. Theapproach method used in this study is a sociological juridical research method, and data analysis in this study usesqualitative analysis methods. The results of research at the Regional General Hospital (RSUD) dr. R. GoetengTaroenadibrata in providing health services to inpatients using BPJS (Social Security Administering Agency) servicesand patients using public services, there are still differences in health services to inpatients using BPJS services(Social Security Organizing Agency) and patients using services In general, the difference is in the room facilities forinpatients. In Purbalingga Regency Regional Regulation Number 3 of 2020 concerning Public Services Article 4, it isclearly stated that there should not be unequal treatment (discrimination) in public services, one of which is relatedto health services. Even so, in the implementation of health services by applying the principle of equal treatment ofpatients, there are still several inhibiting factors. Factors hindering the implementation of the principle of equality oftreatment in terms of health services to inpatients using BPJS services and general services at the Regional GeneralHospital (RSUD) dr. R. Goeteng Taroenadibrata Purbalingga, namely: facilities and infrastructure (room facilities),responsiveness and communication between officers (medical staff) and patients